Functional characterization and expression of endothelin receptors in rat carotid artery: involvement of nitric oxide, a vasodilator prostanoid and the opening of K+ channels in ETB‐induced relaxation - Tirapelli, Carlos R; Casolari, Debora A; Yogi, Alvaro; Montezano, Augusto C; Tostes, Rita C; Legros, Eurode; D'Orléans‐Juste, Pedro; De Oliveira, Ana M (British journal of pharmacology, 2005)
We aimed to functionally characterize endothelin (ET) receptors in the rat carotid artery. mRNA and protein expressions of both ETA and ETB receptors, evaluated by reverse transcription–polymerase chain reaction (RT–PCR) and Western immunoblotting, were detected in carotid segments. Immunohistochemical assays showed that ETB receptors are expressed in the endothelium and smooth muscle cells, while ETA receptors are expressed only in the smooth muscle cells. In endothelium‐denuded vessels, levels of ETB receptor mRNA were reduced. Vascular reactivity experiments, using standard muscle bath procedures, showed that ET‐1 induces contraction in endothelium‐intact and ‐denuded carotid rings in a concentration‐dependent manner. Endothelial removal enhanced ET‐1‐induced contraction. BQ123 and BQ788, selective antagonists for ETA and ETB receptors, respectively, produced concentration‐dependent rightward displacements of the ET‐1 concentration–response curves. IRL1620, a selective agonist for ETB receptors, induced a slight vasoconstriction that was abolished by BQ788, but not affected by BQ123. IRL1620‐induced contraction was augmented after endothelium removal. ET‐1 concentration dependently relaxed phenylephrine‐precontracted rings with intact endothelium. The relaxation was augmented in the presence of BQ123, reduced in the presence of BQ788 and completely abolished after endothelium removal. IRL1620 induced vasorelaxation that was abolished by BQ788 and endothelium removal, but not affected by BQ123. Preincubation of intact rings with NG‐nitro‐L‐arginine methyl ester (L‐NAME), 1H‐[1,2,4]oxadiazolo[4,3‐a]quinoxalin‐1‐one (ODQ), indomethacin or tetraethylammonium (TEA) reduced IRL1620‐induced relaxation. The combination of L‐NAME, indomethacin and TEA completely abolished IRL1620‐induced relaxation while sulfaphenazole did not affect this response. 4‐aminopyridine (4‐AP), but not apamin, glibenclamide or charybdotoxin, reduced IRL1620‐induced relaxation. The major finding of this work is that it firstly demonstrated functionally the existence of both ETA and ETB vasoconstrictor receptors located on the smooth muscle of rat carotid arteries and endothelial ETB receptors that mediated vasorelaxation via NO–cGMP pathway, vasodilator cyclooxygenase product(s) and the activation of voltage‐dependent K+ channels. British Journal of Pharmacology (2005) 146, 903–912. doi:10.1038/sj.bjp.0706388